SIAPA YANG BENAR? “TAFSIR MISIONAL ATAS IMAMAT 19:15 UNTUK MENCARI TITIK TEMU MASALAH BURUH MIGRAN INDONESIA YANG DICAP ILEGAL DI MALAYSIA” - Alvian Apriano (Sekolah Tinggi Teologi Aletheia, 2021)
The pattern of illegal migration that is chosen by some immigrants in Malaysia brings new issues in Indonesia. Such immigrants are considered illegal immigrants or PATI (foreigners without permission) by the Malaysian authority, so their existential rights as a human are being defended. Christian faith recognizes the logic of love in mission, and the measure of the logic of love is the centrifugal act of love. In this case, the PATI who becomes depressed is the center of the act of love. However, the Christian faith also recognizes the text of Leviticus 19:15, which emphasizes justice by acting accordingly. If it is connected with the text, the proper action is that the PATI’s existential rights do not need to be defended because they are “irregular immigrants.” Therefore, by rereading the text of Leviticus 19:15 and tracing it with the perspective of the logic of love in mission and Christian ethics, we can see this issue as indispensable. Pola migrasi ilegal yang dipilih oleh beberapa imigran di Malaysia menjadi persoalan rumit yang berkembang di Indonesia. Bahkan, para imigran yang demikian dianggap pendatang haram atau PATI (Pendatang Asing Tanpa Izin) oleh pihak Malaysia, sehingga dalam dasar itu, hak eksistensial mereka mulai dibela. Iman Kristen mengenal logika kasih dalam bermisi dan tolok ukur logika kasih tersebut ialah tindakan kasih yang sentrifugal, sehingga dalam hal ini para PATI yang menjadi tertekan itu merupakan pusat tindakan kasih. Akan tetapi, iman Kristen juga mengenal teks Imamat 19:15 yang menekankan keadilan dengan tindakan yang sewajarnya. Jika dihubungkan dengan teks tersebut, maka tindakan yang sewajarnya ialah hak eksistensial para PATI tidak perlu dibela, karena mereka imigran yang tidak wajar (tanpa izin). Oleh karena itu, membaca ulang teks Imamat 19:15 dan menelusurinya dengan perspektif logika kasih dalam bermisi dan etika Kristiani memandang persoalan itu sangat diperlukan.